The synthesis and characterisation of a new symmetrical 8,9-bis(hydroxyimino)-4,7,10,13-tetraaza-1,2,15,16-O- dicyclopentylidenehexadecane and its transition metal complexes - Şekerci, Memet (My University, 1999)
8,9-Bis(hydroxyimino)-4,7,10,13-tetraaza-1,2,15,16-O- dicyclopentylidenehexadecane (LH2) was prepared from 1,2-O-cyclopentylidene-4-aza-6-aminohexane (R-NH2) and dichloroglyoxime. The structure of this vic-dioxime has been determined as the (E,E)-form from 1H-NMR and 13C-NMR data. Mononuclear complexes with a metal-ligand ratio of 1:2 have been prepared with Co(II), Cu(II) and Ni(II). The metal-ligand ratio of the U(VI) complex is 1:1 and has dimeric structure. The structure of the ligand and its complexes has been deduced from magnetic susceptibility, elemental analyses, IR, UV-VIS, 1H-NMR, 13C-NMR spectroscopy, TGA and DTA methods.